Correlation between california bearing ratio (CBR) with plasticity index of marine stabilizes soil with cockle shell powder. (November 2019) - Nujid, M M; Idrus, J; Azam, N A; Tholibon, D A; Jamaluddin, D
Abstract: Subgrade soil is important for design purpose of both flexible and rigid pavement structures; flexible and rigid. The quality of flexible and rigid pavement structures is correlated on the strength and stabilization of subgrade layers. The main function of subgrade is to act as a foundation for pavement layers and supporting the load which is transmitted from the overlying layers. The marine soil is a problematic soil which low in strength and do not suitable for road embankment for highway construction. Therefore, the soil strength can be improved by adding stabilizer or admixture to increase its strength. Soil stabilization change its physical and mechanical properties from its original soil. Thus, the physical properties of marine stabilized with cockle shell powder were determined and the potential of Cockle Shell Powder (CSP) as soil stabilizer based on percentage added in CBR test was investigated. Based on previous research, the performance of soil mixed with CSP in the proportion of constant 2.5%, 5%, 7.5% and 10% was examined with CSP properties and California Bearing Ratio (CBR) tests. The results obtained indicates an increment in specific gravity and decreasing in the plastic index (PI) with the addition of 2.5% of CSP. The CBR and PI show a good correlation and thus inclusion of CSP in marine soil could be used as alternative material for subgrade layer in increasing soil strength.